Pemanfaatan Media Sosial Sebagai Alat Untuk Membangun Jaringan Bisnis Dalam Bisnis Dropship: Studi Kasus Pada Mumu Hijab - Resya Dwi Marselina; Intan Dinilah; Meira Purnama Rizki; Sarah Khoirunnisa; Siskia Nur Aini Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
This article or paper aims to determine “the use of social media as a tool for building business networks in the dropship business”. The problem focuses on the use of social media in building business networks. The data collected was obtained based on qualitative observation and analysis, namely interviews with sources directly. This study concludes that the use of social media platforms, especially facebook, can be a means for Mumu Hijab to build a business network, this is proven by the spread of resellers reaching 40 people. Not only that, in building a business network, Mumu Hijab is also active in utilizing WhatsApp, where WhatsApp is a good communication medium for building business networks with Mumu Hijab resellers and also with consumers.